Cold-water coral communities in the Central Mediterranean: aspects on megafauna diversity, fishery resources and conservation perspectives - Capezzuto, Francesca; Ancona, Francesco; Carlucci, Roberto; Carluccio, Angela; Cornacchia, Laura; Maiorano, Porzia; Ricci, Pasquale; Sion, Letizia; Tursi, Angelo; D’Onghia, Gianfranco (Rendiconti Lincei. Scienze Fisiche e Naturali, 2018)
In the last two decades, many new living cold-water coral (CWC) sites throughout the Mediterranean basin have been discovered and investigated. As part of oceanographic cruises, using ROVs and towed cameras, and trawl and longline surveys as well as records from fishermen, a belt of CWC communities has been identified along the Apulian continental margin (Central Mediterranean). The most investigated CWC communities are those of the Santa Maria di Leuca (SML) CWC province (northern Ionian Sea) and Bari Canyon (BC) (southern Adriatic Sea). These communities are mainly structured by the habitat-former species Madrepora oculata and, to a lesser extent, by Lophelia pertusa together with Dendrophyllia cornigera, solitary species, such as Desmophyllum dianthus, black coral, such as Leiopathes glaberrima, sponges (e.g., Pachastrella monilifera, Poecillastra compressa), serpulids, boring clams and colonies of bryozoans. CWC sites are biodiversity hot-spots, that act as “Essential Fish Habitats” for commercial species and through the spill-over effect might contribute to the renewal of stocks in neighbouring fishing grounds, providing ecosystems’ goods and services. Despite their particular features, CWC areas along the Apulian slope are impacted by different anthropogenic activities. Fishermen operate close and around these areas with the aim of obtaining greater catches and sizes of commercial species. Although there are many conservation proposals for CWC habitats and a Fisheries Restricted Area established for Santa Maria di Leuca CWC province, human pressure is still very strong, due to the lack of adequate conservation measures. An effective system of monitoring, control and surveillance will be fundamental to meet the conservation objectives and to reach the Good Environmental Status as part of the Marine Strategy Framework Directive.